Growth Potential of Sunflower Sprouts with Mole Natural Fertilizer or Ecoenzyme from Orange Peel - Fariq Rijal Farras; Nurmahni Harahap; Halimatus Sakdiah Hasibuan (Winaya Inspirasi Nusantara Foundation, 2024)
This research focuses on the utilization of ecoenzymes from the fermentation of organic waste of citrus fruit peel, brown sugar, and water to see the effectiveness of sunflower sprouts plant growth. Experiments were conducted in the science laboratory of MTsN Model 1 Banda Aceh between December 2022 and April 2023 with a complete randomized design factorial pattern (5x4) with 4 replications. The treatments of ecoenzyme (P) were P0 (water), P1 (15 ml ecoenzyme + 385 ml water), P2 (20 ml ecoenzyme + 480 ml water), and P3 (30 ml ecoenzyme + 470 ml water). The results showed a significant interaction between treatments 1, 2, and 3 on plant height and number of leaves. The best results were shown by P3 treatment with 30 ml ecoenzyme and 470 ml water. Although the first week did not show a significant interaction, the other treatments had a significant impact on the observed parameters. Therefore, the use of ecoenzyme from orange peel organic matter can effectively increase the growth of sunflower sprouts.